To join or not to join?–A framework for the evaluation of enterprise blockchain consortia - Schwarzer, Max; Gürpinar, Tan; Henke, Michael (Frontiers in Blockchain, 2022)
Within the past years, enterprise blockchain solutions were frequently developed within different industry consortia. In most cases, this resulted in isolated solutions competing against each other due to similar approaches and goals. Today, decision makers do not necessarily need to establish entirely new blockchain consortia, as established ones already exist, and participation is a considerable way to avoid unreasonable efforts. In this paper, we apply an iterative literature review to identify different factors relevant for practitioners, who face the challenge of joining an existing enterprise blockchain consortium. In a second step, we discuss these factors utilizing supply chain management as a role model. As a main finding, we propose an evaluation framework for the purpose of enterprise blockchain consortium analysis. Additionally, we provide several questions relevant for practitioners during their evaluation stages. With our evaluation framework we contribute to blockchain research, where - despite its high relevance - the topic of consortium evaluation has so far been neglected. We also contribute to research in the field of technology evaluation by proposing and merging five different evaluation dimensions.